2017
DOI: 10.1016/j.amjcard.2017.07.038
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Prognostic Value of the Electrocardiogram in Patients With Acute Occlusion of the Left Circumflex Coronary Artery

Abstract: The utility of the electrocardiogram (ECG) in patients with acute left circumflex (LC) coronary occlusion is not established. This study aimed at determining the clinical, angiographic, and prognostic characteristics associated with the different patterns of ST-segment changes in patients with LC occlusion. A cohort of 314 patients with LC occlusion was categorized according to the admission ECG: (1) ST-segment elevation (ST-E, n=208), (2) isolated ST-segment depression in precordial leads (ST-D, n=62), and (3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…A practical recommendation derived from our study is the pertinence to routinely record the posterior thoracic leads V7 to V9 in patients with acute coronary syndromes based on the high diagnostic yielding of these leads in cases of LCX occlusion. In a series of patients with LCX occlusion (Vives-Borrás et al, 2017) we have found that leads V7 to V9 depict ST segment elevation even in cases showing only a ST segment depression pattern in the whole ECG. In the swine model we have also confirmed that in contrast to LAD or RCA, the LCX occlusion was the only one depicting ST segment elevation in leads V6 to V9 (Vives-Borrás et al, 2018).…”
Section: Discussionmentioning
confidence: 94%
“…A practical recommendation derived from our study is the pertinence to routinely record the posterior thoracic leads V7 to V9 in patients with acute coronary syndromes based on the high diagnostic yielding of these leads in cases of LCX occlusion. In a series of patients with LCX occlusion (Vives-Borrás et al, 2017) we have found that leads V7 to V9 depict ST segment elevation even in cases showing only a ST segment depression pattern in the whole ECG. In the swine model we have also confirmed that in contrast to LAD or RCA, the LCX occlusion was the only one depicting ST segment elevation in leads V6 to V9 (Vives-Borrás et al, 2018).…”
Section: Discussionmentioning
confidence: 94%
“…This result is consistent with a previous study of 314 patients with LCX occlusion, in which proximal LCX occlusion was most frequently observed in patients with ST-segment depression, whereas the distal LCX occlusion was often the culprit artery in the ST-segment elevation group. 11 It is conceivable that the size and location of the culprit artery, the presence of coronary collaterals, and the size of the perfusion territory may play a role in the genesis of the different ST-segment patterns in patients with acute LCX occlusion. Therefore, the precordial ST-segment depression pattern should be interpreted with caution, because these patients appear to have large infarct sizes caused by proximal LCX occlusion, resulting in more advanced acute heart failure.…”
Section: Discussionmentioning
confidence: 99%
“…This result is consistent with a previous study of 314 patients with LCX occlusion, in which proximal LCX occlusion was most frequently observed in patients with ST-segment depression, whereas the distal LCX occlusion was often the culprit artery in the ST-segment elevation group. 11 It is conceivable that the size and location of the for the identification of regional left ventricular wall motion abnormality before coronary angiography. Posterior left ventricular asynergy was identified in 31 (66%), 38 (81%), and 22 (88%) in the No-ST, ST-E, and ST-D groups, respectively (P=0.07).…”
Section: Significance Of St-segment Depressionmentioning
confidence: 99%